Kemampuan Penalaran Matematis Siswa Menggunakan Pendekatan Metaphorical Thinking pada Materi Perbandingan Kelas VIII di SMPN 1 Indralaya Utara - Saputri, Intan; Susanti, Ely; Aisyah, Nyimas (Universitas Hamzanwadi, 2017)
This research is a descriptive research that aims to descrcibe studentsâ mathematical reasoning ability by metaphorical thinking approach in proportion section at grade VIIIA SMPN 1 Indralaya Utara. Data collection technique uses test and interview methods. The test instrument used is included of three reasoning ability problems. Data analysis technique is done by analysing the result of test. The interview is used for supporting the result of studentsâ test. The result of this research shows that the mathematical reasoning ability of students at grade VIIIA of SMP Negeri 1 Indralaya Utara is medium with this details: percentage of students who have mathematical reasoning ability with category excellent is , Â have mathematical reasoning ability with category good, Â have mathematical reasoning ability with category medium, Â have mathematical reasoning ability with category bad, and 0% for mathematical reasoning ability with category very bad. Indicator of mathematical reasoning ability with the highest percentage is presenting written mathematical statement with 91,41% while indicator with the lowest percentage is finding out the pattern or character of mathematical indication for making generalization with 31,25%.